Psychological Themes in Classical Islamic Literature: : A Primary Source Reader - Ansari, Bilal Ali; Elzamzamy, Khalid; Keshavarzi, Hooman; Zaidi, Aamir Azhar (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
Are you curious about the contributions of the Islamic intellectual heritage to the field of psychology? Psychological Themes in the Classical Islamic Literature provides a captivating window into the rich Islamic scholarly tradition as it pertains specifically to human psychology. This book brings together carefully selected, translated, and annotated segments from classical Islamic texts that address enduring questions in psychology. Explore topics like the admissibility and validity of diverse sources of knowledge, the nature of the human psyche and human drives, the mind-body problem, nature versus nurture, dreams, emotions, psychological resilience, and well-being. Discover how Islamic scholars tackled these profound issues generations before their Euro-American counterparts, offering a unique and sophisticated perspective that can enrich modern psychological discourse. Whether a student, scholar, or practitioner, this book is your gateway to appreciating psychology in Islam